(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article discusses the use of various methods in the implementation of traditional educational measures, which are the most important in the education of the young generation. Also, information was given about the need to determine the moral level of the knowledge taught to the future young generation, the need to pay special attention to its upbringing from childhood, and what the results of the implemented measures could be.